KAJIAN KONSISTENSI SIKAP DAN PERBUATAN BERBAHASA INDONESIA BIDANG KEILMUAN - Marsudi Marsudi; Siti Zahrok (JURNAL SOSIAL HUMANIORA (JSH), 2017)
Attitude can be defined as permanent sense, thought, and preference on specific aspect of life. In fact, language attitude of speakers of Bahasa Indonesia  is interesting to be questioned. In relation to this, the aim of this research is to describe consistency in terms of language attitude and language performance among Bahasa Indonesia users. Positive thought and sense toward Bahasa Indonesia should be completely or at least partly actualized on the use of standard language when it is implemented in academic setting.  Cases found in the use of Bahasa Indonesia tend to oppose the essence of language attitude Inconsistency among bahasa Indonesia attitude lies on the level of spelling, diction, and sentence structures The causes of this inconsistency rest on the disparage and ignorance of Bahasa Indonesia language principles The use of Bahasa Indonesia ignoring language principles particularly on academic setting is viewed as unimportant and unurgent matter. Therefore, negative attitude emerges as a result of ignored language principles